Keagenan (Simsar) Sebagai Upaya Menciptakan Lapangan Kerja Bagi Pekerja Yang Mengalami Pemutusan Hubungan Kerja (PHK) di Tengah Wabah Corona Virus Disease (Covid-19) (Perspektif Hukum Ekonomi Syariah) - Dyah Ochtorina Susanti (DIALEKTIKA: Jurnal Ekonomi dan Ilmu Sosial, 2020)
This research is motivated by many employees experience of Termination of Employment due to Corona Virus Disease (Covid-19) pandemic, which causes many people to lose their jobs so that they cannot meet their daily needs, especially employees who have debts in the bank. In this case, a solution is needed so that employees who experience Termination of Employment get a job and can improve the community economy. Research that uses the normative legal research with the statute approach, and conceptual approach, results in the agent (simsar) or better known as agency is an effort that can be done to create jobs for employees who experience Termination of Employment in the middle of the Corona Virus Disease (Covid-19) pandemic. At the end of this study, the authors also give advice to employees who have experienced termination of employment and the community to be more creative and innovative in utilizing technology to get wrong income through agency (simsar).